Quartic fermion self-interactions in two-dimensional gauge theories - Dutra, Alvaro de Souza [UNESP]; Natividade, C. P.; Boschi-Filho, H.; Amaral, R. L P G; Belvedere, L. V. (American Physical Society (APS), 1997)
In this work we discuss the effect of quartic fermion self-interacting terms on the dynamically generated photon masses in 1+1 dimensions, for vector, chiral, and non-Abelian couplings. In the vector and chiral cases we find exactly the dynamically generated mass modified by the quartic term while in the non-Abelian case we find the dynamically generated mass associated with its Abelian part. We show that in the three cases there is a kind of duality between the gauge and quartic couplings. We perform functional as well as operator treatments allowing for the obtention of both fermion and vector field solutions. The structures of the Abelian models in terms of θ vacua are also addressed.